2022
DOI: 10.3390/met12091405
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Mechanical Performance of High Manganese Austenitic Steel

Abstract: High manganese austenitic steel has attracted increasing attention for its application in liquefied natural gas storage tank materials due to its excellent ductility and low cost. This paper presents an overview of the research progress of high manganese austenitic steel in recent years. As a structural material used at a low temperature environment, high manganese steel should not only have certain strength, but also good toughness to prevent brittle fracture at a low temperature. In this work, factors affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Some previous research indicated that MMSs have excellent ductility-strength performance, high surface hardening capability and satisfying wear resistance, which makes them attractive for various wear-dominated industries such as petrochemical, aerospace, shipbuilding, construction and especially the mining industry [7]. Besides, MMSs show a better selfstrengthening effect and higher abrasive impact wear resistance than martensitic and bainitic steels under the continuous medium-or low-impact load, and the wear resistance and work hardening ability of MMSs can be increased by 50-140% and 60-120%, respectively [8][9][10][11][12][13]. LCS, on the other hand, is a good candidate as a base material due to its superior ductility, toughness, and weldability, which enables a lower cost of the resultant bimetal composite compared with the high cost of monolithic MMS layer.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous research indicated that MMSs have excellent ductility-strength performance, high surface hardening capability and satisfying wear resistance, which makes them attractive for various wear-dominated industries such as petrochemical, aerospace, shipbuilding, construction and especially the mining industry [7]. Besides, MMSs show a better selfstrengthening effect and higher abrasive impact wear resistance than martensitic and bainitic steels under the continuous medium-or low-impact load, and the wear resistance and work hardening ability of MMSs can be increased by 50-140% and 60-120%, respectively [8][9][10][11][12][13]. LCS, on the other hand, is a good candidate as a base material due to its superior ductility, toughness, and weldability, which enables a lower cost of the resultant bimetal composite compared with the high cost of monolithic MMS layer.…”
Section: Introductionmentioning
confidence: 99%